Development Of Problem-Based Learning Materials (PBL) In Theme 7 Class 5 At MI Adabiyah 2 Palembang - Tutut Handayani; Hani Atus Sholikhah; Muhammad Agil Muzawir (AIUA Journal of Islamic Education, 2020)
This research aims to: (1) develop Thematic Problem Based Learning (PBL) based Thematic design planning in sub-theme 3, theme 7 class V SD / MI, (2) testing Problem Based Learning (PBL) thematic teaching material on sub-theme 3 , theme 7 class V SD / MI is valid, (3) testing Problem Based Learning (PBL) thematic teaching materials on sub-theme 3, theme 7 class V SD / MI is practical, and (4) testing Problem based Learning (PBL) thematic teaching materials on sub-theme 3, theme 7 class V SD / MI is effective. The research method used is a research and development method with a model developed by Tessmer named formative evaluation which consists of 5 stages: self evaluation, expert review, one-to-one evaluation, small group evaluation, and field test. Data collection used was documentation, questionnaire and test. Data validity test uses a questionnaire at the expert review and one- to-one stage, the practicality of the data uses a questionnaire at the small group stage while the effectiveness test uses a test at the field test stage. The subjects of this study were students of class V 4 MI Adabiyah 2 Palembang with a total of 34 people. The results showed that: (1) design planning thematic based learning problem based learning (PBL) can be used to test its validity which is carried out at the expert review and one to one stage. This can be seen from the evaluation at the self evaluation stage in the form of comments and suggestions used to revise teaching materials to be used as prototype I so that their validity can be tested at a later stage, (2) assessment of the validation questionnaire results conducted at the expert review stage and one to one in the form of scores with an average of 80 so that it is categorized valid, (3) the assessment of the results of the practicality questionnaire carried out on the Small Group in the form of a score of 83 so that it is categorized as very practical, and (4) the assessment of the results of the effectiveness test conducted on the Field Test in the form of a score with an average of 86 so it can be said to be very effective.